Effects of plastic-derived carbon dots on germination and growth of pea (Pisum sativum) via seed nano-priming - Liang, Lili (2023)
Seed nano-priming is a promising technology employed in the agronomic field to promote seed germination and plant growth. However, the effects of carbon dots (CDs) on plant development via seed nano-priming remain unclear. In the present study, CDs synthesized from non-biodegradable plastic wastes were adopted as a nano-priming agent for pea (Pisum sativum) seed treatment. The results demonstrated positive effects of seed priming at all CD concentrations (0.25-2 mg/mL), including accelerated seed germination rate, increased shoot and root elongation, biomass accumulation, and root moisture level compared to the control groups. Surface erosion of seed coat was observed after CD priming, which effectively promoted seed imbibition capability. CD penetration, internalization, and translocation were confirmed using transmission electron microscopy. Furthermore, the CD-plant interaction significantly enhanced seed antioxidant enzyme activity, as well as augmented root vigor, chlorophyll content, and carbohydrate content. These findings exhibit great potential of waste-derived CDs as nano-priming agents for seed germination and seedling development in a cost-effective and sustainable manner.